2016
DOI: 10.4137/cmo.s34542
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Response to Antiangiogenic Therapies in Colorectal Cancer: Where are We Now and What should be Next?

Abstract: Despite advances in the treatment of colorectal cancer (CRC), it remains the second most common cause of cancer-related death in the Western world. Angiogenesis is a complex process that involves the formation of new blood vessels from preexisting vessels. It is essential for promoting cancer survival, growth, and dissemination. The inhibition of angiogenesis has been shown to prevent tumor progression experimentally, and several chemotherapeutic targets of tumor angiogenesis have been identified. These includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 148 publications
0
20
0
Order By: Relevance
“…VEGF is the most widely studied biomarker for predicting response to antiangiogenic treatment 21, 22 . An association between the efficacy of antiangiogenic treatments and VEGF tumor levels has been reported in several studies, with contrasting results 19, 23, 24 .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is the most widely studied biomarker for predicting response to antiangiogenic treatment 21, 22 . An association between the efficacy of antiangiogenic treatments and VEGF tumor levels has been reported in several studies, with contrasting results 19, 23, 24 .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Elevated levels of soluble PDGFRβ in CSF have been found to correlate with brain pericyte injury, suggesting that soluble pericyte cell surface proteins, such as endosialin and PDGFRβ, may be potential biomarkers for ontuxizumab activity. 15,19 Biomarker evaluation demonstrated that circulating endosialin and PDGFRβ in plasma were highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated a potential role for circulating soluble cell surface proteins such as vascular endothelial growth factor receptor in the systemic circulation as biomarkers for pharmacologic and clinical activity of antiangiogenic therapy. 17,18 Elevated levels of soluble PDGFR in CSF have been found to correlate with brain pericyte injury, suggesting that soluble pericyte cell surface proteins, such as endosialin and PDGFR , may be potential biomarkers for ontuxizumab activity. 15,19 Biomarker evaluation demonstrated that circulating endosialin and PDGFR in plasma were highly variable.…”
Section: Responsesmentioning
confidence: 99%
“…Tumor angiogenesis (the formation of new blood vessels) is essential for tumor growth and metastasis (2,4). The development of new blood vessels is a complex phenomenon involving growth factors, extracellular matrix enzymes, endothelial cell migration and proliferation, lumen formation, and anastomosis with other vessels (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…It is the third most common malignancy and second most common cause of cancer-related death in developed countries (2). Intensive surveillance after colorectal cancer surgery improves survival because early diagnosis of recurrence increases the frequency of its curative resection (3).…”
Section: Introductionmentioning
confidence: 99%